2018
DOI: 10.3390/molecules23040985
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Tuberculostatic Activity Evaluation of Novel Benzazoles with Alkyl, Cycloalkyl or Pyridine Moiety

Abstract: Compounds possessing benzimidazole system exhibit significant antituberculous activity. In order to examine how structure modifications affect tuberculostatic activity, a series of benzazole derivatives were synthesized and screened for their antitubercular activity. The compounds 1–20 were obtained by the reaction between o-diamine, o-aminophenol, or o-aminothiophenol with carboxylic acids or thioamides. The newly synthesized compounds were characterized by IR, 1H-NMR, 13C-NMR spectra, and elemental analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We noted that 6ak is a core structure of an antituberculosis agent. 19 The catalytic system also worked well with terminal alkenes, resulting in linear products ( 6al and 6am ) in 72–77% yields with good regioselectivity ( L : B = ≥92 : 8).…”
Section: Resultsmentioning
confidence: 90%
“…We noted that 6ak is a core structure of an antituberculosis agent. 19 The catalytic system also worked well with terminal alkenes, resulting in linear products ( 6al and 6am ) in 72–77% yields with good regioselectivity ( L : B = ≥92 : 8).…”
Section: Resultsmentioning
confidence: 90%
“…Because glycoside 5 has a larger dipole moment (8.8680 D) and partition coefficient (−0.97), it may be poorly absorbed by cells and show lower activity. 39 The in vitro antifungal activity proved that glycosylation of HYM could enhance its antifungal activity, but not all sugar units and glycosidic bonds were acceptable. Combined with the structure−activity analysis obtained by quantum chemistry, we found that the glycosylation site of HYM must be located on the hydroxyl group.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Glycoside 15 has a smaller dipole moment (8.2293 D) and partition coefficient (−1.42) than glycoside 5 . Because glycoside 5 has a larger dipole moment (8.8680 D) and partition coefficient (−0.97), it may be poorly absorbed by cells and show lower activity …”
Section: Resultsmentioning
confidence: 99%
“…The study described below is a continuation of our previous studies on amidrazone derivatives exhibiting high anti-tuberculosis activity [ 7 , 8 , 9 , 10 , 11 , 12 ]. The previous studies allowed us to formulate a hypothesis that the planarity of these molecules being isoniazid analogues (INH) is a significant prerequisite for their tuberculostatic activity.…”
Section: Introductionmentioning
confidence: 88%